Peningkatan Hasil Belajar Siswa pada Pelajaran Matematika dengan Menggunakan Metode Bermain Peran Siswa Kelas 1 SD - Warsinah Warsinah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The background of this classroom action research is the importance of learning application that is fun and more significance in conveying a concept on mathematics learning activities at 1st grade of SD Negeri 1 Kualasimpang and a lack of students’ understanding on the sum of story form, so that the results are less than the maximum. Based on those problems, through this research is expected to provide solution. The solution is to apply the method of learning to play role that can make students more active in the learning process and can improve the students’ learning result. This research uses classroom action research (CAR). This research is implemented by the class teacher with three stages, they are: planning, implementation, and reflection. Implementation of the act is done in a collaborative and participatory, in order to improve the performance and management of the classroom. The data collection techniques for this research are observation and testing technique, while the data analysis technique uses quantitative descriptive analysis technique. This research is implemented by two cycles. Each cycle is held two meetings. Teacher activity in the cycle I is 69 %, in the cycle II is 88 %. Student activity in the cycle I is 51 %, in the cycle II is 83 %. And the learning result in the cycle I is obtained the percentage of classical completeness by 50% and in the cycle II is 80%. Based on the result of research, it can be conclude that the application of the role play method in mathematics by summing in story form can improve learning result and students activity at 1st grade of SD Negeri 1 Kualasimpang.